Results of the ADHERE upper airway stimulation registry and predictors of therapy efficacy. (14th September 2019) - Thaler, Erica; Schwab, Richard; Maurer, Joachim; Soose, Ryan; Larsen, Christopher; Stevens, Suzanne; Stevens, Damien; Boon, Maurits; Huntley, Colin; Doghramji, Karl; Waters, Tina; Kominsky, Alan; et al.
Abstract : Objective/Hypothesis: The ADHERE Registry is a multicenter prospective observational study following outcomes of upper airway stimulation (UAS) therapy in patients who have failed continuous positive airway pressure therapy for obstructive sleep apnea (OSA). The aim of this registry and purpose of this article were to examine the outcomes of patients receiving UAS for treatment of OSA. Study Design: Cohort Study. Methods: Demographic and sleep study data collection occurred at baseline, implantation visit, post‐titration (6 months), and final visit (12 months). Patient and physician reported outcomes were also collected. Post hoc univariate and multivariate analysis was used to identify predictors of therapy response, defined as ≥50% decrease in Apnea‐Hypopnea Index (AHI) and AHI ≤20 at the 12‐month visit. Results: The registry has enrolled 1, 017 patients from October 2016 through February 2019. Thus far, 640 patients have completed their 6‐month follow‐up and 382 have completed the 12‐month follow‐up. After 12 months, median AHI was reduced from 32.8 (interquartile range [IQR], 23.6–45.0) to 9.5 (IQR, 4.0–18.5); mean, 35.8 ± 15.4 to 14.2 ± 15.0, P  < .0001. Epworth Sleepiness Scale was similarly improved from 11.0 (IQR, 7–16) to 7.0 (IQR, 4–11); mean, 11.4 ± 5.6 to 7.2 ± 4.8, P  < .0001. Therapy usage was 5.6 ± 2.1 hours per night after 12 months. In a multivariate model, only female sex and lower baseline body mass index remained as significant predictors of therapy response. Conclusions: Across a multi‐institutional study, UAS therapy continues to show significant improvement in subjective and objective OSA outcomes. This analysis shows that the therapy effect is durable and adherence is high. Level of Evidence: 2 Laryngoscope, 130:1333–1338, 2020